2022
DOI: 10.3390/s22228645
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Fusarium oxysporum Infection in Processing Tomatoes (Solanum lycopersicum) and Pathogen–Soil Interactions Using a Low-Cost Portable Electronic Nose and Machine Learning Modeling

Abstract: The early detection of pathogen infections in plants has become an important aspect of integrated disease management. Although previous research demonstrated the idea of applying digital technologies to monitor and predict plant health status, there is no effective system for detecting pathogen infection before symptomatology appears. This paper presents the use of a low-cost and portable electronic nose coupled with machine learning (ML) models for early disease detection. Several artificial neural network mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Feng et al [ 65 ] reported early detection of Fusarium oxysporum infection in tomato processing using a low-cost portable electronic nose with a classification accuracy in the range of 84–95%.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al [ 65 ] reported early detection of Fusarium oxysporum infection in tomato processing using a low-cost portable electronic nose with a classification accuracy in the range of 84–95%.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the case of Fol, this indication came up to 49 days before the manifestation of visual symptoms (Table 1, Row 7) and an average of 35.2 days before any morphological symptoms were observable. Other studies have reported a decline in vascular flow or water loss slightly before the appearance of wilt symptoms in infected plants (Feng et al, 2022;Street & Cooper, 1984;Wang et al, 2012). To document this, Wang et al (2012) and Feng et al (2022) used a Li-6400 gas exchange system (Li-Cor Inc.); whereas Street and Cooper (1984) used a Scholander pressure bomb.…”
Section: Early Detection Of Diseasementioning
confidence: 99%
“…Other studies have reported a decline in vascular flow or water loss slightly before the appearance of wilt symptoms in infected plants (Feng et al, 2022;Street & Cooper, 1984;Wang et al, 2012). To document this, Wang et al (2012) and Feng et al (2022) used a Li-6400 gas exchange system (Li-Cor Inc.); whereas Street and Cooper (1984) used a Scholander pressure bomb. In contrast to the simple assessment using the PlantArray system, the aforementioned methods are time-consuming and laborious.…”
Section: Early Detection Of Diseasementioning
confidence: 99%
“…The Bloodhound ® ST214′s efficacy in detecting disease presence by analyzing VOCs emitted by tomato plants infected with powdery mildew ( Oidium neolycopersici ) in greenhouse settings compared to healthy controls was demonstrated [ 137 ]. Similarly, a low-cost, portable e-nose combined with machine learning algorithms was used to accurately detect Fusarium oxysporum in tomato plants and soil samples [ 138 ], while Sun et al [ 139 ] were successful in detecting B. cinerea infection in tomatoes. A PEN 3, Win Muster Air-sense Analytics E-nose was used to identify infections caused by three fungi— Botrytis spp., Penicillium spp., and Rhizopus spp.—in strawberries [ 140 ].…”
Section: Cannabis Pathogens: Symptoms and Management Approaches At Di...mentioning
confidence: 99%